The Impact of Superficial Vessel Density on Glaucoma Progression according to the Stage of Glaucoma - Jiyun Lee (MDPI AG, 2021)
Purpose: To investigate the clinical significance of vessel density (VD) on visual field (VF) progression regarding the severity of glaucoma. Methods: A total of 130 eyes were recruited in this retrospective and longitudinal study. Superficial and deep VDs in circumpapillary and macular regions were measured via ImageJ. The rate of VF progression was defined as the mean deviation (MD) slope (dB/year). Linear regression was used to verify factors affecting deterioration of VF. The eyes with lower superficial VD were further analyzed. Results: Fifty patients with early glaucoma (EG) (MD > −6 dB) and 52 patients with moderate-to-advanced glaucoma (MAG) (MD ≤ −6 dB) were included. A faster progression rate was found in MAG (p = 0.049). Superficial VD was noticeably related to the VF progression rate in total eyes and in MAG (Both Ps ≤ 0.007, respectively). With patients in the lower half of the superficial VD, the VD was significantly associated with the rate of progression (B, 0.049, p = 0.021). This association was independent of the baseline MD and OCT parameters. Conclusion: Decreased superficial VD might conversely affect the progression of glaucoma even in MAG, which suggests superficial VD could be used as a potential marker to foresee the disease progression even in progressed eyes.